Cardiac remodeling in rats with renal failure shows interventricular differences - Svíglerová, Jitka; Kuncová, Jitka; Nalos, Lukás; Holas, Jaromír; Tonar, Zbynek; Rajdl, Daniel; Stengl, Milan (Experimental biology and medicine (Maywood, N.J.), 2012)
Chronic renal failure (CRF) is associated with an increased incidence of cardiovascular diseases. Intensive research revealed a number of alterations in the heart during CRF; however, possible interventricular differences in CRF-induced cardiac remodeling have so far not been addressed. CRF was induced by two-stage surgical 5/6 nephrectomy (NX) in male Wistar rats. Cellular hypertrophy was quantified using immunohistological morphometric analysis. Contraction force and membrane potential were recorded in left and right ventricle papillary muscles with an isometric force transducer and high-resistance glass microelectrodes. Hypertrophy was present in the left ventricle (LV) of NX animals, but not in the right ventricle (RV) of NX animals, as documented by both ventricle/body weight ratios and cellular morphometric analysis of the cross-sectional area of myocytes. The contraction force was reduced in the LV of NX animals but increased in the RV of NX animals compared with sham-operated rats. Rest potentiation of contraction force was relatively more pronounced in the LV of NX rats. Fifty percent substitution of extracellular sodium with lithium significantly increased the contraction force only in the LV of NX animals. Action potential durations were shortened in both ventricles of CRF animals. Cardiac structural and contractile remodeling in CRF shows significant interventricular differences. CRF induces hypertrophy of the LV but not of the RV. LV hypertrophy was associated with a reduction of contraction force, whereas in the RV, the contraction force was enhanced. Partial recovery of contractile function of the LV by rest potentiation or lithium substitution indicates a role of the Na(+)/Ca(2+) exchanger in this phenomenon.
Keywords: Membrane Potentials; srdeční komory; Male; hypertenze; Rats, Wistar; Kidney Failure, Chronic; Lithium Compounds; náhodné rozdělení; chronické selhání ledvin; mužské pohlaví; sloučeniny lithia; Hypertrophy, Left Ventricular; potkani Wistar; Hypertension; Ventricular Remodeling; nefrektomie; membránové potenciály; krysa rodu Rattus; Myocardial Contraction; kardiovaskulární nemoci; Animals; zvířata; Rats; Random Allocation; kontrakce myokardu; Heart Ventricles; Cardiovascular Diseases; Ventricular Function; Nephrectomy; remodelace komor; srdce - funkce komor; hypertrofie levé komory srdeční